Prostaglandin E2 role in inhibition of joint cartilage collagen destruction in patients with osteoarthritis - E V Chetina; D DiBattista; A R Pool (Научно-практическая ревматология)
Prostaglandin E2 role in inhibition of articular cartilage collagen degradation in patients with osteoarthritis. Objective. To assess prostaglandin E2 (PGE2) role in inhibition of type II collagen digestion in explants of articular cartilage of pts with osteoarthritis (OA). Material and methods. Explants of articular cartilage of pts with OA were cultured with PGE2 1pg to 10 ng/ml. Type II collagen digestion was assessed with immuno-enzyme assay. Gene expression was evaluated with PCR in real time. Results. PGE2 10 pg/ml as well as transforming growth factor β2 (TGFβ2) suppressed type II collagen digestion in explants of articular cartilage of pts with OA. This concentration of PGE2 did not suppress proteoglycan (aggrecan) degradation. Gene expression analysis in 5 OA pts showed that PGE2 10 pg/ml suppressed metallomonooxigenase (MMP)-13, MMP-1 and marker of chondrocyte hypertrophy type X collagen (COL10A1) as well as proinflammatory cytokines interleukine (IL)-1β and tumor necrosis factor (TNF)α. Naproxen, nonselective cyclooxygenase(COX)-2 and 1 inhibitor concentration from 5 to 30 mcg/ml blocked TGFβ2 induced collagen digestion inhibition proving that PGE2 mediate influence of this growth factor. Naproxen concentration 5 mcg/ml increased collagen degradation. Conclusion. The study showed that PGE2 is a chondroprotector because it is able to suppress selectively OA pts cartilage collagen degradation. Beside that cartilage chondrocyte hypertrophy in OA connected functionally with increased collagen digestion is also regulated by low concentrations of PGE2